Measurement of streaming potential coupling coefficient on a clean sandstone for downhole monitoring applications [electronic resource] - Shazana Mohd. Zaki, 1988- (2011)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2011